Parental Involvement in the Implementation of Personal Hygiene Practices for Students with Special Needs - Munirah Md Sofi; Mohd Hanafi Mohd Yassin (Department of Special Education, 2022)
This study aims to identify the level of parental involvement in the implementation of personal hygiene practices for children with special needs in Klang district. This study used a quantitative design, a survey study that utilized questionnaire method in data collection. The questionnaire instrument used in this study was taken from the previous study and modified according to the research objectives. The reliability value for the instrument was 0.87 and this instrument had been validated by two experts in the field of special education and language. The questionnaires were distributed using Google Form to the target parents. A total of 100 parents were selected by simple random sampling as respondents. Data obtained through the questionnaires were analyzed using ‘Statistical Package for the Social Science’ (SPSS) version 23.0 in the form of descriptive analysis. The findings showed that the total mean score for the knowledge level of parents was 4.70 which was very high. Meanwhile, the mean score level for the parental involvement in the personal hygiene care of students with special needs was 4.47, which was also very high. The findings also showed that there was a significant relationship between the knowledge and practice of parents in the hygiene care of special needs students. In conclusion, the level of parental involvement was very high in the hygiene practice of students with special needs in Klang district. It is hoped that this study can increase the awareness of personal hygiene among students with special needs through the role played by the parents.